2019
DOI: 10.18203/2319-2003.ijbcp20191010
|View full text |Cite
|
Sign up to set email alerts
|

Price variation in different brands of anticancer drugs available in Indian pharmaceutical market: a cost analysis study

Abstract: Background: Cancer is one of the most expensive and lethal noncommunicable diseases globally. Availability and affordability of anticancer drugs are the most important factors on which management of cancer depends. The objective of the study was to evaluate the variation of cost among different brands of anti-cancer drugs available in the Indian market.Methods: “Current Index of Medical Specialties” July-October 2018 and “Drug Update” Sept - 2018 were used to obtain cost in INR* (Indian National Rupees) of ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
4
1
Order By: Relevance
“…Our findings discovered that prices of various biologic drugs manufactured by different brands in India show a wide variation in the minimum and maximum prices. In our study, however, rituximab 100 mg showed a cost variation of 201.94%, but the study by Adwal SK et al (2018) [ 15 ] showed a cost variation of 40%. This was likely due to the changes in the prices set by the manufacturers.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…Our findings discovered that prices of various biologic drugs manufactured by different brands in India show a wide variation in the minimum and maximum prices. In our study, however, rituximab 100 mg showed a cost variation of 201.94%, but the study by Adwal SK et al (2018) [ 15 ] showed a cost variation of 40%. This was likely due to the changes in the prices set by the manufacturers.…”
Section: Discussioncontrasting
confidence: 80%
“…(2018) [15] showed a cost variation of 40%. This was likely due to the changes in the prices set by the manufacturers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Adwal and Baghel's study reported high-cost variation with alkylating agent carboplatin 150 mg injection i.e. 1100% and lowest with antimetabolite anticancer agent cytarabine 500 mg injection 6.56% [27]. Another study by Tadesse and Fang from Ethiopia shows that the lowest price generic anticancer medicines were sold 1.29 and 2.62 times the international reference price in the public and private sectors [28].…”
Section: Discussionmentioning
confidence: 96%
“… 5 52 However, we are reassured that our country estimate of ALL treatment costs was broadly similar to that calculated by Faruqui et al 27 using a similar but not identical treatment regimen and recognising wide variations in prices of different brands of the same anticancer drug in the same dose and dosage form manufactured in India. 37 …”
Section: Discussionmentioning
confidence: 99%